Chip Diplomacy: Chip War Taiwan, People’s Republic China and United States and its Implications for Indonesia - Latief, Mohammad Nurdin Al; Mahroza, Jonni; Priyanto, Priyanto; Widodo, Pujo; Sutanto, Rudy; Patmi, Sri; Prakoso, Lukman Yudho (PT FORMOSA CENDEKIA GLOBAL, 2024)
The main goal of this research is to analyze the implications of chip war between PRC, US and Taiwan and its implications to Indonesia. This research uses a qualitative descriptive approach to gain an in-depth understanding and description of the phenomenon or issues related chip war between PRC, US and Taiwan and its implication to Indonesia. Result and findings is During the 1970s, the Taiwanese government established the Industrial Technology Research Institute, tasked with conducting research in the realm of silicon chips. The United States and China are competing to dominate the semiconductor industry. Taiwan has become the world's largest chip production center. The political situation between the United States, Taiwan, and China is heating up. Taiwan holds a key position in global semiconductor production.